Implementation of Laws And Animal Relief Livestock Reviewed From Article 549 KUHP - Ahmad, Muhammad Al Habsy (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2024)
The aimed of this study; First, to describe how the implementation of the law on abandoning livestock is reviewed from Article 549 of KUHP. Second, to find out the factors that hinder the enforcement of the law on abandoning livestock. This type of research is normative legal research, namely legal research carried out by examining materials library or secondary data. Data collection techniques in this research are: Literature Study. Furthermore, for data analysis, the researcher uses all data consisting of primary data and secondary data (primary, secondary and tertiary legal materials) which will be processed and analyzed qualitatively. The results of this research are:1) that the implementation of the law is reviewed from Article 549 of the Criminal Code regarding the abandonment of livestock in Regent Regulation Number 21 of 2021 concerning amendments to Regent Regulation Number 34 of 2018 concerning Control of Livestock Animals, it could be said that appropriate in its application, according to the results of the researcher, namely suitability of objectives, principles that can be implemented, clarity of formulation, law enforcement, analysis process and implementation formulation, appropriate program preparation. In the process of enforcement and action against negligence livestock, as the agency authorized for non-judicial control, Satpol-PP and fire brigade (DAMKAR). The handling and enforcement process follows Article 549 of the Criminal Code, such as fines being given to violators and confiscation of the violators' livestock.